Intense Pulsed Plus Low-Level Light Therapy in Meibomian Gland Dysfunction - Marta, Ana (2021)
Purpose: To analyse the clinical outcome in patients with meibomian gland dysfunction (MGD) who underwent intense pulsed light (IPL) plus low-level light therapy (LLL). Materials and methods: The prospective non-comparative study included identified by MGD patients with altered interferometry and lower loss area of the meibomian glands (LAMG), who underwent IPL plus LLL, between July 2020 and August 2020. A multimodal assessment was performed before, 2-3 weeks, and 6 months after treatment. The main outcome was lipid layer thickness (LLT) and the secondary outcomes were the ocular surface disease index (OSDI) score, presence of corneal fluorescein staining (CFS), blink rate (BR), Schirmer test (ST), tear meniscus height (TMH), tear osmolarity (OSM), non-invasive break-up time (NIBUT) and LAMG. Results: This study included 62 eyes of 31 patients, 61.3% female, with a mean age of 66.94±9.08 years at the time of IPL plus LLL treatment. LLT (<0.001) grades improved 6 months after treatment. The mean OSDI score improved (p<0.001) from 45.02±21.17 (severe symptoms) to 22.35±17.68 (moderate symptoms) at 2-3 weeks and 8.24±17.9.91 (normal) at 6 months after treatment. CFS was identified in 51.6% (32/62) before and in 45.2% (28/62) 6 months (p=0.293) after treatment. ST (p=0.014) grades improved; OSM grades mild worsened (p<0.001); TMH, NIBUT and LAMG grades did not modify 6 months after treatment. No patient suffered any adverse effects. Conclusion: IPL combined with LLL was effective and safe, improving the lipid layer thickness in MGD and decreasing the level of symptoms.